Perilaku Penggunaan Masker pada Petani Padi yang Terpapar Pestisida: Studi Kualitatif Berdasarkan Theory of Planned Behavior - Erwin Nur Rif'ah; Erzhya Zahra Aurora; Ayu Kusnugraha N; Pinaka Dya Ivena; Risky Dwi Prasetya (Jurnal Persada Husada Indonesia, 2026)
Research Objective. To explore mask-wearing behavior among rice farmers who apply pesticides in Antirogo Urban Village, Jember Regency, using the Theory of Planned Behavior (TPB). Methodology. This descriptive qualitative study was conducted from April to May 2026. Eleven informants participated: ten rice farmers as main informants and the head of the farmer group as a key informant. Data saturation was reached in interviews with the ten main informants, while the key informant provided contextual information. Data were obtained through in-depth interviews, direct observation during pesticide spraying, and documentation and were analyzed using the interactive model of Miles, Huberman, and Saldaña. Results. Five TPB-related themes comprising 15 categories were identified: attitude, subjective norms, perceived behavioral control, intention, and behavior. Farmers generally recognized the protective value of face coverings and the health risks of pesticide exposure, but many described heat, breathing difficulty, and discomfort. Family and peer encouragement was weak, access and field conditions constrained use, and intentions were easily disrupted by situational barriers. Only two main informants used a face covering consistently throughout spraying; other practices were inconsistent or absent. Conclusion. Positive beliefs alone did not ensure consistent protection. Interventions should combine risk communication, supportive family and peer norms, field supervision, and access to comfortable respiratory protective equipment selected in accordance with pesticide-use guidance.